2023
DOI: 10.1007/s13167-022-00309-x
|View full text |Cite
|
Sign up to set email alerts
|

Clarifying sleep characteristics and analyzing risk factors of sleep disorders to promote a predictive, preventive, and personalized medicine in patients with burn scars

Abstract: Purpose This study assessed sleep quality in patients with burn scars and investigated risk factors of sleep disorders to guide clinical therapy. From the strategy of predictive, preventive, and personalized medicine (PPPM/3PM), we proposed that risk assessment based on clinical indicators could prompt primary prediction, targeted prevention, and personalized interventions to improve the management of sleep disorders present in patients with burn scars. Methods This ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 82 publications
0
1
0
Order By: Relevance
“…This finding may be explained with the results of Liu et al who found an increased risk of allergic conjunctivitis, resulting from decreased level of Catenibacterium. 76 Children with allergic conjunctivitis have a 2.35-fold higher incidence and risk of myopia compared with children without allergic conjunctivitis. 77 Nonetheless, there is limited research on Catenibacterium in relation to the eye.…”
Section: Discussionmentioning
confidence: 99%
“…This finding may be explained with the results of Liu et al who found an increased risk of allergic conjunctivitis, resulting from decreased level of Catenibacterium. 76 Children with allergic conjunctivitis have a 2.35-fold higher incidence and risk of myopia compared with children without allergic conjunctivitis. 77 Nonetheless, there is limited research on Catenibacterium in relation to the eye.…”
Section: Discussionmentioning
confidence: 99%
“…By using techniques like inverse variance weighted (IVW) estimation, Zhang et al ultimately reached their conclusion that attention deficit hyperactivity disorder was not related to allergic conjunctivitis [9]. Since previous observational studies show growing evidence that gut microbiota associate with the incidence of AC closely, Liu et al came to the conclusion that gut microbiota may be involved in immunomodulation and lower the incidence of allergic conjunctivitis, except for Oscillospira flora, which produces substances linked to inflammatory diseases and contributes to the incidence of allergic conjunctivitis [10]. To further estimate genetic associations between polyunsaturated fatty acids and allergy disorders, a two-sample MR analysis was used to identify that: omega-3 fatty acids had a preventive effect on the development of AC, while omega-6:3 fatty acids raised the risk of AC, taking into account age, economic status, BMI, and daily behavioral habits [11].…”
Section: Conjunctivitismentioning
confidence: 99%
“…Among these, anxiety is a common annoying problem, often due to patient’s concerns about their appearance, the painful nature of therapeutic procedures (i.e., wound debridement, wound dressing change, and repair surgeries), and monetary and occupational problems [ 11 13 ]. In addition to high anxiety, recent surveys documented poor perceived sleep quality following burn injuries, which could be experienced mainly due to pain, narrow airway, pruritus, and scar appearance during different stages of the recovery process [ 14 16 ]. Studies also show a bivariate relationship between anxiety and sleep disturbances among burn sufferers so that high burn-induced anxiety leads to insomnia and poor sleep quality; sleep deprivation also triggers or exacerbates anxiety [ 17 ].…”
Section: Introductionmentioning
confidence: 99%